An analysis of the implementation of integrated development : a case study of Ekurhuleni Metropolitan Municipality - Tshiyoyo, Mudikolele Michel (University of Pretoria, 2022)
Dissertation (MAdmin (Public Management and Policy))--University of Pretoria, 2021.